Fused filament fabrication of conductive polymer on textile for wearable - Raguraman Gunasellan (Nanyang Technological University, 2023)
This study investigates the application of conductive filaments through 3D printing, specifically utilizing Fused Filament Fabrication (FFF) printers, on diverse fabric types. The growing interest in smart textiles and flexible electronics has spurred advancements in material science and manufacturing. However, a critical knowledge gap exists regarding the adhesion dynamics of 3D printed conductive filaments to various fabric types, particularly with different weave patterns. Understanding these dynamics is crucial for establishing reliable connections in applications like wearable technology and medical devices, making it necessary to bridge these gaps for the broader field's benefit.